THE EFFECT OF LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK MOTIVATION TO THE WORK SATISFACTION OF EMPLOYEES AT SUNGAI PENUH CITY YOUTH AND SPORTS SERVICE - ., H Juharman; Heryanto (Archives of Business Research, 2019)
This research is aimed to know and to analysis the effect of leadership style, work environment and work motivation to the work satisfaction of employees at Sungai Penuh City Youth and Sports Service. 40 employees at Dinas Pekerjaan Umum Kota Sungai Penuh are the population in this research. Census method was used as as the technique of sampling because there were only 40 employees. Primary data were used as the type of the data, while the data were collected by using questionnaires with Likert scale. Instrument tests, conducted in the research, were validity and reliability tests. The data were analysed by using data description test, classic assumption test, and hypothesis test. Results of the research shows that a commitment of an organization has positive and significant effects to employees’ work performance at Dinas Kepemudaan dan Olah Raga Kota Sungai Penuh and work discipline has positive and significant effects to the employees’ work performance at Dinas Kepemudaan dan Olah Raga Kota Sungai Penuh.